2014
DOI: 10.1038/ncomms5645
|View full text |Cite
|
Sign up to set email alerts
|

Male–female communication triggers calcium signatures during fertilization in Arabidopsis

Abstract: Cell–cell communication and interaction is critical during fertilization and triggers free cytosolic calcium ([Ca2+]cyto) as a key signal for egg activation and a polyspermy block in animal oocytes. Fertilization in flowering plants is more complex, involving interaction of a pollen tube with egg adjoining synergid cells, culminating in release of two sperm cells and their fusion with the egg and central cell, respectively. Here, we report the occurrence and role of [Ca2+]cyto signals during the entire double … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
145
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(152 citation statements)
references
References 70 publications
7
145
0
Order By: Relevance
“…These results and characterization of LLG1, a putative paralog of LRE, indicate that LRE/ LLG1 interacts with FER in the ER lumen and functions as a chaperone to bring FER to the FA . Once localized to the FA, LRE could function as a coreceptor with FER to perceive signals from the pollen tube to trigger calcium profile changes and ROS production (Denninger et al, 2014;Duan et al, 2014;Ngo et al, 2014). However, the amino acid residues in LRE that are important for it to function in pollen tube reception are not yet clear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results and characterization of LLG1, a putative paralog of LRE, indicate that LRE/ LLG1 interacts with FER in the ER lumen and functions as a chaperone to bring FER to the FA . Once localized to the FA, LRE could function as a coreceptor with FER to perceive signals from the pollen tube to trigger calcium profile changes and ROS production (Denninger et al, 2014;Duan et al, 2014;Ngo et al, 2014). However, the amino acid residues in LRE that are important for it to function in pollen tube reception are not yet clear.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, ROS produced in the female gametophyte are important for pollen tube reception, and ROS-mediated pollen tube rupture requires calcium (Duan et al, 2014). Indeed, changes in cytoplasmic calcium ([Ca 2+ ] cyto ) observed during pollen tube-synergid interactions (Iwano et al, 2012;Denninger et al, 2014;Hamamura et al, 2014) showed that the initiation of calcium oscillations and the increase in [Ca 2+ ] cyto are affected in fer and lre mutant synergids (Ngo et al, 2014). In addition to affecting ROS and calcium production in ovules, LRE also has an intracellular role in chaperoning FER from the endoplasmic reticulum (ER) to the FA of the synergids .…”
Section: Introductionmentioning
confidence: 99%
“…However, the distribution of FER as the key receptor was not affected, suggesting that post-Golgi secretion was not compromised by defective vacuolar acidification. A more likely scenario is that proton homeostasis affects ROS and Ca 2+ spiking, which have recently been shown to mediate pollen tube reception (13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…Male ligands are yet to be identified. However, recent studies showed that the production of reactive oxygen species (ROS) and Ca 2+ spiking are downstream events of FER-controlled pollen tube reception (13)(14)(15)(16).…”
mentioning
confidence: 99%
“…[23][24][25][26] It has been indicated that polyspermy block functions in the egg cell [27][28][29][30] and the central cell 30 to promote faithful double fertilization 31 . In addition, Ca 2C -dependent egg activation occurs in plants as well as animals, [32][33][34] and it has been postulated that the increased Ca 2C level triggers the polyspermy block of fertilized egg cells via Ca…”
Section: Polyspermy and Polyspermy Blockmentioning
confidence: 99%